Mga kagamitang panturo sa paglinang ng kasanayan sa pagsulat ng salaysay para sa unang taon sa kolehiyo - Tumangan, Alcomtiser P. 1932- (1979)
This research presented instructional materials for developing communication skills, particularly in writing. The materials are specifically intended for first year college students with courses in Pilipino I. The study also aimed to prepare students for creative writing in Filipino.
Appendices: leaves 194-209
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Teaching -- Aids and devices; Creative writing (Higher education).